Point‐Combination Transect (PCT): Incorporation of small underwater cameras to study fish communities. Issue 6 (20th February 2019) - Widmer, Lukas; Heule, Elia; Colombo, Marco; Rueegg, Attila; Indermaur, Adrian; Ronco, Fabrizia; Salzburger, Walter
Abstract: Available underwater visual census (UVC) methods such as line transects or point count observations are widely used to obtain community data of underwater species assemblages, despite their known pit‐falls. As interest in the community structure of aquatic life is growing, there is need for more standardized and replicable methods for acquiring underwater census data. Here, we propose a novel approach, Point‐Combination Transect (PCT), which makes use of automated image recording by small digital cameras to eliminate observer and identification biases associated with available UVC methods. We conducted a pilot study at Lake Tanganyika, demonstrating the applicability of PCT on a taxonomically and phenotypically highly diverse assemblage of fishes, the Tanganyikan cichlid species‐flock. We conducted 17 PCTs consisting of five GoPro cameras each and identified 22, 867 individual cichlids belonging to 61 species on the recorded images. These data were then used to evaluate our method and to compare it to traditional line transect studies conducted in close proximity to our study site at Lake Tanganyika. We show that the analysis of the second hour of PCT image recordings (equivalent to 360 images per camera) leads to reliable estimates of the benthic cichlid community composition in Lake Tanganyika according to species accumulation curves, while minimizing the effect of disturbance of the fish through SCUBA divers. We further show that PCT is robust against observer biases and outperforms traditional line transect methods. Foreign Language Abstract Zusammenfassung: Trotz der bekannten Schwächen dieser Methoden, werden Unterwasser‐Zensusverfahren, wie zum Beispiel das Linien‐Transsekt oder die Punkzählung, feldübergreifend benutzt um Daten zu Lebensgemeinschaften und deren Artenzusammensetzung zu erheben. Mit zunehmendem Interesse an der Struktur von aquatischen Lebensgemeinschaften wächst auch die Nachfrage nach standardisierten und replizierbaren Methoden um solche Daten zu erheben. Wir präsentieren hier eine neue Methode, das Punkt‐Kombinations Transsekt (PCT), welches auf Aufnahmen von kleinen Unterwasserkameras beruht und dadurch den Einfluss des Experimentators und Identifizierungsfehler minimiert. Zur Illustration dieser Methode haben wir am Tanganjika‐See in Sambia eine Pilotstudie durchgeführt um die Anwendbarkeit der PCT auf einer taxonomisch und phänotypisch diversen Lebensgemeinschaft von Fischen, den Buntbarschen, zu demonstrieren. 17 PCTs wurden durchgeführt, jeweils bestehend aus fünf GoPro Kameras. Mit den Bildern konnten insgesamt 22, 867 Buntbarschindividuen identifiziert und 61 Arten zugewiesen werden. Als Qualitätsanalyse haben wir die gesammelten Daten mit denen von klassischen Linien‐Transsekt Studien verglichen, welche in unmittelbarer Nähe des Standortes der Pilotstudie durchgeführt wurden. Wir zeigen, dass durch die Analyse der jeweils zweiten Stunde, der im PCT aufgenommenen Bilder (entspricht 360 Bildern pro Kamera) eine solide Quantifizierung der benthischen Buntbarsch Lebensgemeinschaft im Tanganjika See möglich ist. Zudem wird der Störeffekt durch Taucher minimiert. Ausserdem können wir demonstrieren, dass PCT eine gewisse Resistenz gegen subjektive Datenverzerrung durch einen Beobachtereffekt hat und in dieser Hinsicht konventionelle Linien‐Transsekte überlegen ist.